A light touch intervention with a heavy lift – gender, space and risk in a global vaccination programme. Issue 12 (2nd December 2022) - Kalbarczyk, Anna; Closser, Svea; Hirpa, Selamawit; Cintyamena, Utsamani; Azizatunnisa, Lutfhi; Agrawal, Priyanka; Rahimi, Ahmad Omid; Akinyemi, Oluwaseun O.; Mafuta, Eric M.; Deressa, Wakgari; Alonge, Olakunle O.
ABSTRACT: Frontline workers (FLWs) in the Global Polio Eradication Initiative go door-to-door delivering polio vaccine to children. They have played a pivotal role in eliminating wild polio from most countries on earth; at the same time, they face significant bodily risk. STRIPE, an international consortium, conducted a mixed-methods study exploring the knowledge and experiences of polio staff in seven countries (Afghanistan, Bangladesh, Democratic Republic of Congo, Ethiopia, India, Indonesia and Nigeria). We surveyed 826 polio FLWs and conducted semi-structured interviews with 22 of them. We used a body work framework to guide analysis. Polio workers perform a different kind of body work than many other FLWs. Delivering a few drops of oral vaccine takes a light touch, but gendered spaces can make the work physically dangerous. Polio's FLWs must bend or break gendered space norms as they move from house-to-house. Navigating male spaces carries risk for women, including lethal risk, particularly in conflict settings. Workers manoeuvre between skeptical community members and the demands of supervisors which generates emotional labour. Providing FLWs with more power to make operational decisions and providing them with robust teams and remuneration would improve the likelihood that they could act to improve their working conditions.